Degree for slain commando: UUM to award posthumous qualification to cop during convocation - The, Star (The Star, 2013)
ALOR SETAR: A police commando killed in a gunbattle with armed Sulu intruders in Kampung Tanduo, Lahad Datu, in March will receive a posthumous degree at the Universiti Utara Malaysia's 26th convocation here later this month.Asst Supt Zulkifli Mamat (pic), 46,who died on March 1, had finished his bachelor's degree in communication before he was deployed to Sabah.The commando's widow, Noraziah Nor, 28,is expected to receive the scroll during the fourday convocation at the university's Dewan Muadzam Shah in Sintok, near here,that starts on Nov 30.